The "other" students : Filipino Americans, education, and power - Maramba, Dina C.; Bonus, Rick, 1962- (Emerald Publishing Limited : Information Age Publishing Inc., 2013)
Though the Filipino American population has increased numerically in many areas of the United States, especially since the influx of professional immigrants in the wake of the 1965 Immigration Act, their impact on schools and related educational institutions has rarely been documented and examined. The Other Students: Filipino Americans, Education, and Power is the first book of its kind to focus specifically on Filipino Americans in education. Through a collection of historical and contemporary perspectives, we fill a profound gap in the scholarship as we analyze the emerging presence of Filipino Americans both as subjects and objects of study in education research and practice. We highlight the argument that one cannot adequately and appropriately understand the complex histories, cultures, and contemporary conditions faced by Filipino Americans in education unless one grapples with the specificities of their colonial pasts and presents, their unique migration and immigration patterns, their differing racialization and processes of identity formations, the connections between diaspora and community belonging, and the various perspectives offered by ethnic group-centered analysis to multicultural projects. The historical, methodological, and theoretical approaches in this anthology will be of interest to scholars, researchers, and students in disciplines which include Education, Ethnic Studies, Asian American and Pacific Islander Studies, Anthropology, Sociology, Political Science, Urban Studies, Public Policy, and Public Health.